Physical activity of community-dwelling adults with traumatic spinal cord injuries in the Cape Metropole - Aeysha Gabriels; Toughieda Ismail; Lucian Bezuidenhout; Conran Joseph (South African Journal of Physiotherapy)
Background: Physical activity (PA) is an important indicator for disease prevention in adults with spinal cord injuries (SCIs). Regular PA can improve functioning, community reintegration, economic participation and overall well-being.